Effect of High-Pressure Processing on Fresh Sea Urchin Gonads in Terms of Shelf Life, Chemical Composition, and Microbiological Properties - Valentina Coroneo; Francesco Corrias; Andrea Brutti; Piero Addis; Efisio Scano; Alberto Angioni (Foods, 2022)
Paracentrotus lividus is a widespread sea urchin species appreciated worldwide for the taste of its fresh gonads. High-pressure processing (HPP) can provide a thermal equivalent to pasteurization, maintaining the organoleptic properties of the raw gonads. This study evaluated HPP technology’s effect at 350 MPa and 500 MPa on microbial inactivation and biochemical characteristics of P. lividus gonads. HPP at 350 MPa resulted in a higher decrease in protein and free amino acids associated with a loss of olfactory, color, and gustatory traits and a visual alteration of the texture. On the other hand, gonad samples stored for 40 days after treatments at 500 MPa showed a good organoleptic profile similar to fresh gonads. Furthermore, only 500 MPa effectively reduced mesophilic bacteria contamination among the two HPP treatments carried out. Total lipids increased during storage; however, the SAFA/PUFA rate was homogeneous during HPP trials ranging from 2.61–3.91 g/100 g. Total protein decreased more than 40% after HPP at 350 MPa, whereas, after 500 MPa, it remained stable for 20 days. The amount of free amino acid constantly decreased during storage after HPP at 350 MPa and remained constant at 500 MPa. HPP can effectively remove the bacterial flora and inactivate enzymes, maintaining the properties of the fresh sea urchin gonads.